تأثير طريقة الثواب والعقاب في التحصيل تعليم مادة اللغة العربية لطلاب المدرسة المتوسطة الأهلية نور الهداية سيماطركس, باسامان - ميسرة, ميسرة; حسني, أرمان (Darul Yasin Al Sys, 2024)
This study aims to determine how the effect of reward and punishment methods in improving student learning outcomes at Madrasah Tsanawiyah Swasta Nurul Hidayah Simatorkis, Pasaman. This research was conducted on class VIII students of MTsS Nurul Hidayah Simatorkis in the academic year 2022/2023. The research method used in this research is the experimental method. The hypothesis proposed that the reward and punishment method affects student learning outcomes at MTsS Nurul Hidayah Simatorkis, Pasaman, data obtained from the results of the tests distributed. In this population, the reward and punishment method mostly affects student learning outcomes at MTsS Nurul Hidayah Simatorkis, Pasaman.